Characterization of sleep apnea among a sample of adults from Samoa - Lacey W. Heinsberg; Alysa Pomer; Brian E. Cade; Jenna C. Carlson; Take Naseri; Muagututia Sefuiva Reupena; Satupa'itea Viali; Daniel E. Weeks; Stephen T. McGarvey; Susan Redline; Nicola L. Hawley (Sleep Epidemiology)
Sleep apnea is a global public health concern, but little research has examined this issue in low- and middle-income countries, including Samoa. The purpose of this study was to examine the sample prevalence and characteristics of sleep apnea using a validated home sleep apnea device (WatchPAT, Itamar) and explore factors that may influence sleep health in the Samoan setting. This study used data collected through the Soifua Manuia (“Good Health”) study, which investigated the impact of the body mass index (BMI)-associated genetic variant rs373863828 in CREBRF on metabolic traits in Samoan adults (sampled to overrepresent the obesity-risk allele of interest). A total of 330 participants had sleep data available. Participants (53.3 % female) had a mean (SD) age of 52.0 (9.9) years and BMI of 35.5 (7.5) kg/m2, and 36.3 % of the sample had type 2 diabetes. Based on the 3 % and 4 % apnea hypopnea indices (AHI) and the 4 % oxygen desaturation index (ODI), descriptive analyses revealed moderate to severe sleep apnea (defined as ≥15 events/hr) in 54.9 %, 31.5 %, and 34.5 % of the sample, respectively. Sleep apnea was more severe in men (e.g., AHI 3 % ≥15 in 61.7 % of men and 48.9 % of women). Correction for non-representational sampling related to the CREBRF obesity-risk allele resulted in only slightly lower estimates. Multiple linear regression linked a higher number of events/hr to higher age, male sex, higher BMI, higher abdominal-hip circumference ratio, and geographic region of residence. Further research and an increased focus on equitable and affordable diagnosis and access to treatment are crucial to addressing sleep apnea in Samoa and globally.